Hilton Cafe International, Atop the Better Living Center at the New York World's Fair - 1964-1965
Food Favorites from Hilton Hotel kitchens around the world are featured in this colorful restaurant and outdoor terrace high in the sky overlooking the New York World's Fair. Try a snack or a meal from one of the five open kitchens representing South and Latin America, Europe, the Mediterranean, the Orient, and North America. The prices are moderate and the beverage service includes international favorites.